Factors associated with uptake of contraceptives among HIV positive women on dolutegravir based anti-retroviral treatment-a cross sectional survey in urban Uganda - Leah Mbabazi; Mariah Sarah Nabaggala; Suzanne Kiwanuka; Juliet Kiguli; Eva Laker; Arthur Kiconco; Stephen Okoboi; Mohammed Lamorde; Barbara Castelnuovo (BMC, 2022)
Abstract Background In May 2018, following the preliminary results of a study in Botswana that reported congenital anomalies in babies born to HIV-positive women taking dolutegravir drug, the WHO issued a teratogenicity alert. However, there are scarce data on the impact of this guidance on contraceptive uptake among women taking dolutegravir. We assessed the uptake of contraceptives in HIV-positive women of reproductive age on dolutegravir regimens. Methods We conducted a cross-sectional survey from April 2019 to July 2019 in five government health facilities in central Uganda, where dolutegravir-based regimens were offered as the preferred first-line antiretroviral treatment. We randomly selected 359 non-pregnant women aged 15-49 years taking dolutegravir-based regimens and interviewed them using semi-structured interviewer-administered questionnaires. We collected data on demographics, contraceptive use, individual, social, and health system factors. We described patients' characteristics using descriptive statistics and assessed factors associated with contraceptive uptake using a modified Poisson regression model. Results A total of 359 women were included in the study. The mean age was 37 years (standard deviation = 6.8) and overall contraceptive uptake was 38.4%. The most utilized method was injectable method at 58.4% followed by condoms (15%), intrauterine device (10.7%), pills (6.4%), implants (5.4%), and sterilization (0.7%). Predictors for contraceptive uptake were parity of 3-4 children (Adjusted Prevalence Ratio (APR) = 1.48, 95% confidence interval (CI): 1.14, 1.92) in reference to those with 1-2 children. There was reduced contraceptive uptake in women of the age range 40-49 years (APR = 0.45, CI: 0.21-0.94) compared to those aged 15-24 years. Unemployed women were less likely to use contraceptives (APR: 0.6, CI: 0.42- 0.94) than the formally employed. Contraceptive uptake was lower among women who did not discuss family planning with their partners (APR = 0.39, CI: 0.29-0.52) than those who discussed family planning with their partners and women who did not receive family planning counseling (APR = 0.56, CI: 0.34-0.92) than those who received family planning counselling. Conclusion We observed a low-level uptake of contraceptives, with injectables as the most used method. Family planning counseling and partner discussion on family planning were associated with contraceptive uptake among the women who used dolutegravir-based regimens. There is a need for more strategies to integrate FP services and increase male involvement in HIV care programs.